2012
DOI: 10.5751/es-04959-170321
|View full text |Cite
|
Sign up to set email alerts
|

Food-Carbon Trade-offs between Agriculture and Reforestation Land Uses under Alternate Market-based Policies

Abstract: ABSTRACT. Understanding the effects of payments on the adoption of reforestation in agricultural areas and the associated food-carbon trade-offs is necessary to inform climate change policy. Economic viability of reforestation under payment per hectare and payment per tonne schemes for carbon sequestration was assessed in a region in southern Australia supporting 6.1 Mha of rain-fed agriculture. The results show that under the median scenario, a carbon price of 27 A$/tCO 2 -e could make onethird of the study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 52 publications
0
42
0
Order By: Relevance
“…Similarly, Haines-Yong et al (2012) confirmed a trade-off between the provisioning services ("crop-based production") and regulating services ("habitat diver-sity"). Also, during the process of ecological restoration, which converted the agricultural land back into natural ecosystems, trade-offs can be found among different ecosystem services, such as trade-off between biodiversity and salinity mitigation (Maron and Cockfield, 2008), between carbon sequestration and species conservation , food production (Paterson and Bryan, 2012), and water supply (Chisholm, 2010). While, as humans play a critical role in managing the agroecosystem, political practices, socioeconomic incentives and technological progresses are likely to influence the quantity and quality of ecosystem services, which will further affect the direction of trade-offs (Nelson et al, 2009).…”
Section: Trade-offs In Ecosystemsmentioning
confidence: 99%
“…Similarly, Haines-Yong et al (2012) confirmed a trade-off between the provisioning services ("crop-based production") and regulating services ("habitat diver-sity"). Also, during the process of ecological restoration, which converted the agricultural land back into natural ecosystems, trade-offs can be found among different ecosystem services, such as trade-off between biodiversity and salinity mitigation (Maron and Cockfield, 2008), between carbon sequestration and species conservation , food production (Paterson and Bryan, 2012), and water supply (Chisholm, 2010). While, as humans play a critical role in managing the agroecosystem, political practices, socioeconomic incentives and technological progresses are likely to influence the quantity and quality of ecosystem services, which will further affect the direction of trade-offs (Nelson et al, 2009).…”
Section: Trade-offs In Ecosystemsmentioning
confidence: 99%
“…This equates to determining 'carbon carrying capacity' (Roxburgh et al, 2006). The potential of plantations to replenish C on deforested semiarid to mesic arable land in southern Australia was estimated by Paterson and Bryan (2012). Our work is thematically similar, but we use a finer spatial scale, simulate natural (autonomous, unmanaged) regrowth, allow a longer duration, and to reflect the higher error margins in rangeland, we calculate at a coarser economic scale.…”
Section: Dsocmentioning
confidence: 99%
“…The non-linear growth formulation typically used in evenaged forestry (e.g. Waterworth et al, 2007) has been used to model reforestation by semiarid plantations (Paterson and Bryan, 2012). The function has two dependent variables (the potential biomass and the age of fastest growth, called 'G' -the inflection point of the growth curve).…”
Section: Biomass Growth Modellingmentioning
confidence: 99%
“…This is a key challenge for government at all levels and research organizations to meet. Paterson and Bryan (2012) tackle an issue that has been of growing concern over the past decades, namely the impact on landscape and NRM caused by policies designed to produce environmental benefits in conjunction with maintenance of http://www.ecologyandsociety.org/vol18/iss1/art32/ productive farming and forestry. Such policies have been widespread from the mid-1980s in the European Union, following the creation of Environmentally Sensitive Areas (Hanley et al 1998, Wilson et al 2007, and in the United States, where the Conservation Reserve Program (Rao et al 2007, Sullivan et al 2004) and farmland preservation schemes have a long history (Dorfman et al 2009, Hellerstein andNickerson 2002).…”
Section: Developing Modelsmentioning
confidence: 99%
“…Working in the lower reaches of Australia's Murray-Darling Basin, Paterson and Bryan (2012) quantified food-carbon trade-off curves at a landscape scale employing two commonly used market-based carbon policy instruments, namely payments per tonne and payment per hectare. Their analysis reveals that large areas of agricultural land could become more profitable as carbon sinks even with relatively modest carbon prices.…”
Section: Developing Modelsmentioning
confidence: 99%